TEACHERS’ SCAFFOLDING TALK IN EFL CLASSROOM INTERACTION (A CASE STUDY AT SMAN 17 MAKASSAR) - Syamsidar, Syamsidar; Baa, Sultan (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The objective of the study was to discover teachers’ scaffolding talk in EFL classroom interaction. The study employed case study design. The study was conducted at SMA 17 Makassar South Sulawesi. The data were obtained from classroom observation, semi-structured interview and questionnaire. In determining the participants, the researcher used purposive sampling approach taking one experienced teacher in that school. The data from observation and interview were analyzed by using data analysis procedure consisting of data collection, data condensation and conclusion drawing or verifying. The result of this study showed that: (1) there were five types of teacher’s scaffolding talk. They are modelling, explaining, inviting students’ participation, instructing, and questioning. From those types, it was found that all type of teachers’ scaffolding talk based on Wood (1995) occurred; (2) Scaffolding talks can facilitate the behavioral engagement of the students in EFL Classroom Interaction, such as paying more attention, attempting to ask question to the teacher, attempting to answer the question from the teacher and actively seeking for the information